2016
DOI: 10.1016/j.psyneuen.2015.12.017
|View full text |Cite
|
Sign up to set email alerts
|

Acute stress alters autonomic modulation during sleep in women approaching menopause

Abstract: Hot flashes, hormones, and psychosocial factors contribute to insomnia risk in the context of the menopausal transition. Stress is a well-recognized factor implicated in the pathophysiology of insomnia; however the impact of stress on sleep and sleep-related processes in perimenopausal women remains largely unknown. We investigated the effect of an acute experimental stress (impending Trier Social Stress Task in the morning) on presleep measures of cortisol and autonomic arousal in perimenopausal women with an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 51 publications
3
16
0
Order By: Relevance
“…These findings extend our previous work showing altered regulatory control of blood pressure during sleep (de Zambotti et al, IN PRESS) and an altered autonomic profile in response to pre-sleep stress, in women with MTI (de Zambotti et al, 2016). Autonomic hyperarousal is thought to play a role in the etiology of insomnia disorder, with several studies finding higher HR and abnormal ANS modulation in insomnia disorder in mixed groups of men and/or women of varying ages (Bonnet and Arand, 2010; Riemann et al, 2015).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These findings extend our previous work showing altered regulatory control of blood pressure during sleep (de Zambotti et al, IN PRESS) and an altered autonomic profile in response to pre-sleep stress, in women with MTI (de Zambotti et al, 2016). Autonomic hyperarousal is thought to play a role in the etiology of insomnia disorder, with several studies finding higher HR and abnormal ANS modulation in insomnia disorder in mixed groups of men and/or women of varying ages (Bonnet and Arand, 2010; Riemann et al, 2015).…”
Section: Discussionsupporting
confidence: 90%
“…None of the previous studies focused on MTI, although we recently reported that women with MTI have elevated beta EEG activity in REM sleep reflecting heightened EEG arousal compared to controls (Baker et al, 2015). We also previously demonstrated (de Zambotti et al, 2016) that women with MTI have blunted vagal recovery during the night following an experimental pre-sleep stressor, suggesting altered ANS function, at least in response to stress.…”
Section: Introductionsupporting
confidence: 54%
“…Chronic stress could add a layer of complexity to PSG sleep disturbance in insomnia disorder in midlife women – Hall et al 138 found that women with more chronic stress exposure over a 9-year period had greater PSG-assessed WASO (as well as being more likely to have insomnia) than participants with moderate stress exposure. We also found that women with insomnia showed less within-night recovery in autonomic vagal functioning following pre-sleep acute stress exposure 144 as well as raised HR 145 and raised blood pressure 91 during sleep relative to women without insomnia, also in the menopausal transition.…”
Section: Sleep Disorders In the Context Of The Menopausal Transition mentioning
confidence: 52%
“…In premenopausal women, hormonal changes, flushes and psychosocial factors contribute to increasing the frequency of insomnia. It has been demonstrated that there is more electro-encephalographic activation and a lack of vascular activity recovery after acute stress in women with insomnia, indicating that the latter contributes to increasing stress sensitivity [ 110 ].…”
Section: Part II the Effects Of Sleep On Healthmentioning
confidence: 99%